Trees make soil conservation pay - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Trees in grass strips, trees on contoured bench terraces, trees on bank and ditch structures and trees contour-planted in hedgerows represent four ways in which trees can help to control soil erosion. They also supply fodder, fuelwood, timber and...